In vitro synthesis of the full-length complement of the negative-strand genome RNA of vesicular stomatitis virus. - Testa, D (1980)
Under the normal conditions of in vitro RNA synthesis, the virion-associated RNA polymerase of vesicular stomatitis virus synthesizes five monocristronic mRNAs and a 48-nucleotide-long leader RNA that represents the exact 3'-terminal region of the genome RNA [Colonno, R. J. & Banerjee, A. K. (1978) Cell, 15, 93-101]. When the transcribing core was preincubated with ATP and CTP, reisolated, and then incubated in the presence of the beta, gamma imido analogue of ATP (AdoPP[NH]P) and the three normal ribonucleoside triphosphates, the full-length complementary strand of the genome RNA was synthesized in vitro. The results suggest that specific phosphorylated states of regulatory proteins may control transcription in vitro to generate the full-length plus strands.